Consumer Protection in Sharia Financial Products: A Review from the Perspective of Sharia Economic Law - Rajindra Rajindra; Muthmainnah MD (Universitas Muhammadiyah Palu, 2025)
Consumer protection in Sharia financial products is an essential aspect of ensuring fairness, transparency, and legal certainty within the Islamic economic system. This study examines the principles, mechanisms, and legal frameworks governing consumer protection from the perspective of Sharia economic law. Using a normative legal research approach, the analysis focuses on key Sharia principles such as justice (al-‘adl), transparency (al-shaf?fiyyah), and the prohibition of deceptive practices (gharar and tadlis). The findings reveal that Sharia economic law provides a comprehensive foundation for consumer protection through contractual requirements, ethical guidelines, and dispute resolution mechanisms based on Islamic legal traditions. The study also highlights the importance of regulatory reinforcement and institutional supervision to ensure that Sharia financial institutions uphold consumer rights. Strengthening legal instruments and increasing public awareness are recommended to enhance consumer trust and support the growth of the Sharia financial industry.